2006
DOI: 10.1577/t05-213.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Population Structure of Remnant Lake Sturgeon Populations in the Upper Great Lakes Basin

Abstract: Abstract.-Populations of lake sturgeon Acipenser fulvescens have undergone dramatic declines in abundance and distribution in the Great Lakes basin and are a species of conservation concern throughout their range. While information regarding the genetic population structure of this species is critical for the development of effective management plans, little information currently exists. We examined both microsatellite and mitochondrial DNA (mtDNA) variation as a means of estimating population genetic diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
111
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(119 citation statements)
references
References 51 publications
6
111
2
Order By: Relevance
“…Consequently, homing to natal sites can facilitate the evolution of beneficial site-specific genotypic and phenotypic adaptation over time. In sturgeon species, existing data suggest some degree of homing associated with natal philopatry (Auer, 1996;Stabile et al, 1996;Tranah et al, 2001), resulting in genetically distinct populations (DeHaan et al, 2006;Welsh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, homing to natal sites can facilitate the evolution of beneficial site-specific genotypic and phenotypic adaptation over time. In sturgeon species, existing data suggest some degree of homing associated with natal philopatry (Auer, 1996;Stabile et al, 1996;Tranah et al, 2001), resulting in genetically distinct populations (DeHaan et al, 2006;Welsh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Our genetic-based approach to detecting migration eliminates this problem. The development of highly variable genetic markers, such as microsatellite DNA, has allowed for discrimination among different lake sturgeon populations (DeHaan et al, 2006;Welsh et al, 2008), thereby facilitating assignment of population of origin on an individual basis. Numerous studies on sturgeon species have successfully utilized multi-locus microsatellite genotyping techniques for a variety of purposes (Stabile et al, 1996;Tranah et al, 2001;Israel et al, 2004;Bott et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat degradation and fragmentation by dams continues to decrease their abundance and impede restoration efforts (Schueller and Hayes, 2011) by altering spawning behavior and reducing recruitment (Auer, 1996b;Haxton and Findlay, 2008). Despite significant declines in abundance, neither this study nor others (DeHaan et al, 2006;Drauch and Rhodes, 2007;Welsh et al, 2008;McDermid et al, 2011;Wozney et al, 2011) have observed significant decreases in genetic variability or evidence of inbreeding within populations of Lake Sturgeon. It is believed that the sturgeon are buffered from expected losses of genetic diversity because of their longevity and overlapping generations.…”
Section: Discussionmentioning
confidence: 53%
“…Neraas and Spruell, 2001;Meldgaard et al, 2003;Yamamoto et al, 2004). For some long-lived threatened and endangered fish species, however, observed anthropogenic declines in population abundance have not been mirrored by similar genetic changes (DeHaan et al, 2006;Lipp e et al, 2006;Reid et al, 2008;McDermid et al, 2011;Wozney et al, 2011). The long generation times of these species may buffer against genetic loss within and among river fragments over the time scales studied to date (Lipp e et al, 2006;Reid et al, 2008;McDermid et al, 2011;Wozney et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Pairwise estimates of genetic divergence suggest that the greatest levels of structure exist among populations originating from different major drainages, concordant with previous findings (McQuown et al 2003). Significant genetic differentiation was observed among several populations within drainages, including comparisons between fish from the Sturgeon River and Peshtigo River (Great Lakes Basin), as found by DeHaan et al (2006). This indicates that for lake sturgeon, the selection of a within-drainage source population for reintroductions might be preferable to reduce the possibility of outbreeding depression.…”
Section: Discussionmentioning
confidence: 78%